El maravilloso mago de Oz - Baum, L. Frank (Lyman Frank), 1856-1919.; Villarino, Bea. (Madrid : Mestas Ediciones, 2000)
After being transported by a cyclone to the land of Oz, Dorothy and her dog are befriended by a scarecrow, a tin man, and a cowardly lion, who accompany her to the Emerald City to look for a wizard who can help Dorothy return home to Kansas.
Translation of: The wonderful wizard of Oz.
Keywords: Fantasy; Fantasia